Pathological and Immuno-Molecular Examination of Protozoa in Aborted Fetus’s and Placenta of Iraqi Cattle (A case report) - Hashim, Muna Sachit; Mahmood, Thikra Abdulla; Ali J. AL-Nuaimi; Hassan, Mayada S.; Yousif, Eman Hashim; Humadai, Taghreed Jabber; Alramah, Hana Salih Abd Ali; Abdulkhaleq, Layth Abdulmajeed; Ali, Angham Jasem Mohammed (Journal of Kerbala for Agricultural Sciences, 2022)
Tissue samples of placenta and aborted fetus were collected from aborted cow and preserved in 10% formalin buffered saline for routine histopathology stained with H&E and for immunohistochemistry to detect TNF-a marker. Pathological examination showed necrotic foci with abscesses mainly around site of invasive protozoa. Immuno-Molecular examination showed marked deposition of TNF marker in tissue, mainly brain of fetus, which refers to genetic damage in gene responsible for controlling TNF values. It is concluded that protozoal infection with Neospora caninum can cause abortion in cattle at advanced stage (8th month ) of gestation with severe histopathological lesions on placenta as well as the brain of fetus. This case report is an update for the information presented in the Proceedings of the 3rd Scientific Conference of the Faculty of Veterinary Medicine / University of Kerbala on 10th April 2017.